The Impact of Bank Structure on Small Business and Small Farm Lending - Steven G. Craig; Polly T. Hardee (Journal of Entrepreneurial Finance, 2001)
This paper empirically explores the impact of bank size, holding company affiliation and the degree of branching on small business and farm lending through a conceptual analysis encompassing private information asymmetries inherent in these bank dependent borrowers. The study expands the literature by removing the influence of capital constraints in bank dependent lending through comparing real estate secured to non real estate loans in a reduced form model. Furthermore, it encompasses an allocation analysis over bank dependent loans, its large loan counterpart and other assets. Overall the findings indicate that not only small banks, but instate and more particularly one bank holding company banks devote more of their assets to small business and farm loans. Banks owned by out-of-state holding companies do not. Low to moderately branched banks are also active in these markets. In this respect the smaller, more simply structured bank may possess a relative advantage in the bank dependent loan market arising from the capacity to mitigate acute informational asymmetries.
Keywords: L25; G21; Q14; L11; 650; Firm Performance; Banks; Depository Institutions; Microfinance; Mortgages; Financing Policy; Financial Risk; Risk Management; Capital Structure; Valuation; Goodwill; Agricultural Finance; Farm Lending; Small Business Lending